Collaboration Between Teachers and Parents on Mental Health of High School Students and Adolescents - Nabila Zulfa Fauziyyah; Naura Raysa Azkia Ahmad; Suparmi (Aslim: Journal of Education and Islamic Studies, 2025)
The obvious increase in the number of cases of depression and burnout makes the mental health of high school students a crucial topic that fundamentally hinders their academic success and psychosocial well-being. The purpose of this study is to analyze and formulate an ideal model of cooperation between teachers and parents as a basis for comprehensive support. The data comes from five different scientific articles, both quantitative, qualitative, and editorial, which were synthesized to form an applicable theoretical framework. The results of this review developed the Supportive Alliance model, which highlights that effective collaboration must be based on trust, competence, and two-way communication. The main findings emphasize that emotional support from the home environment is the most important factor, and this collaboration needs to incorporate mental resilience skills training as well as self-management to strengthen students' internal aspects. Although the Supportive Alliance model has a strong conceptual basis, this study found significant shortcomings in its implementation, primarily due to the high resource requirements and the urgency to create measurable operational guidelines, as well as the integration of professional clinical experts in handling high-risk cases.